INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN INOVATIF DI SEKOLAH DASAR - Mu?min Saud, Abdul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2015)
The development of science, technology and information (science and technology) is very fast and globalization nowadays occur positive and negative impacts on people's lives, both individual and social life. The positive impact of the development of science and technology and the globalization of the labor market is opening opportunities in accordance with the needs of society and the state. While the negative impact is the changing values and norms of life that is often in contradiction with the norms and values of life that has existed in the community. In this context, education, especially primary education, plays a very important to preserve and protect the norms and positive life values that already exist in the society of a country from the negative effects of science and technology development and globalization. The education process is right and quality provided supplies and power to maintain the "identity" of the negative effects of globalization, not only for the interests of individual learners, but also for the benefit of society and the state. National policy development of the noble character education into the national education system is a strategic effort to equip future generations with the noble character of the nation as the identity of Indonesia in global competition. With the character education that is applied systematically and sustainably, a child will be emotionally intelligent. Emotional intelligence is important provision in preparing children to meet the future, because someone will be more easily and successfully face all kinds of life challenges, including the challenge to succeed academically.